The Risk-Taking Channel of Monetary Policy in Norway - Artashes Karapetyan (Norges Bank, 2016)
We identify the effects of monetary policy on credit risk-taking using a unique dataset covering the population of corporate borrowers in Norway. We find that a lower benchmark interest rate (interbank rates or overnight rates) induces the average bank to grant more loans to risky firms. We also find that the strength of the bank's balance-sheet is important: less capitalized banks are more likely to increase loan volumes to ex-ante risky firms compared to more capitalized ones (Jimenez et al., 2014). The data allow us to distinguish the changes in the supply of credit from the changes in credit demand. In all our specifications we control for both observed and unobserved firm and bank heterogeneity by using financial statement information and firm, bank and time fixed effects.
hdl:11250/2495729
Keywords: E44; E5; G01; G21; G28; L14; 330; risk-taking channel; monetary policy; financial stability; credit risk